Securities regulation and implicit penalties - Donghua Chen; Yuyan Guan; Gang Zhao; Feifei Wu (China Journal of Accounting Research, 2011)
The extant literature offers extensive support for the significant role played by institutions in financial markets, but implicit regulation and monitoring have yet to be examined. This study fills this void in the literature by employing unique Chinese datasets to explore the implicit regulation and penalties imposed by the Chinese government in regulating the initial public offering (IPO) market. Of particular interest are the economic consequences of underwriting IPO deals for client firms that violate regulatory rules in China's capital market. We provide evidence to show that the associated underwriters' reputations are impaired and their market share declines. We further explore whether such negative consequences result from a market disciplinary mechanism or a penalty imposed by the government. To analyze the possibility of a market disciplinary mechanism at work, we investigate (1) the market reaction to other client firms whose IPO deals were underwritten by underwriters associated with a violation at the time the violation was publicly disclosed and (2) the under-pricing of IPO deals undertaken by these underwriters after such disclosure. To analyze whether the government imposes an implicit penalty, we examine the application processing time for future IPO deals underwritten by the associated underwriters and find it to be significantly longer than for IPO deals underwritten by other underwriters. Overall, there is little evidence to suggest that the market penalizes underwriters for the rule-violating behavior of their client firms in China. Instead, the Chinese government implicitly penalizes them by imposing more stringent criteria on and lengthening the processing time of the IPO deals they subsequently underwrite.
Keywords: G18; 650; IPO; Government regulation; Implicit penalties; Underwriter